Public Relations Strategy In Running Partnership Program In PT. Plantation Nusantara Vii Unit Padang Pelawi - Hendra Pranata; Yanto Yanto; Bayu Risdiyanto (Penerbit Jurnal Indonesia, 2021)
Public relations strategy really needs to be carried out by an organization or agency to form a positive image of the company. The importance of public relations apart from being a liaison and conveying information to the public, is also a good environmental shaping tool for public understanding of information and company policies. PT. Perkebunan Nusantara VII Unit Padang Pelawi in building a positive image in the partnership program. The purpose of this study was to determine the public relations strategy in running the partnership program at PT. Perkebunan Nusantara VII Unit of Padang Pelawi. This study uses a qualitative descriptive method, by making descriptions and descriptions in a systematic, factual and accurate manner regarding the facts and characteristics and relationships between the phenomena being investigated by collecting data and then analyzing it to obtain conclusions. The data collection technique was done by means of interviews, observation and documentation. From the results of this study, it can be said that the public relations strategy in running the partnership program at PT. Perkebunan Nusantara VII Unit of Padang Pelawi very good, this is because policies related to implementation guidelines, work methods, procedures and regulations carried out by the company are in accordance with the company's standard operating procedures, in addition to the partnership fund assistance program as well as information and technology assistance, which have a positive impact on company employees (internal) and society (external).